2018
DOI: 10.1080/15538362.2018.1470594
|View full text |Cite
|
Sign up to set email alerts
|

Profitability and Technical Efficiency of Pineapple Production in Ogun State, Nigeria

Abstract: Nigeria pineapple production remains low when compared to other producing nations. The production output of the crop has been attributed to inefficient use of available inputs. This study focused on profitability and technical efficiency of pineapple production. Two Agricultural Development Project zones with three blocks each were randomly selected from the study area. The blocks consist of six cell-units each from which 101 pineapple farmers were selected. Data from interviews were analysed using descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
8
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 8 publications
7
8
1
2
Order By: Relevance
“…Production of pineapple could be increased by increasing human labour cost as the coefficient is significantly positive, the average increase being 0.34% for a 1% increase in human labour cost. Similar findings have been reported by several researches [31,32,33]. Again, Table 2 exhibits that the sigma square (0.052) of the estimated model is statistically significant at 1% level of probability.…”
Section: Empirical Results Of the Stochastic Production Frontier Modelsupporting
confidence: 88%
See 1 more Smart Citation
“…Production of pineapple could be increased by increasing human labour cost as the coefficient is significantly positive, the average increase being 0.34% for a 1% increase in human labour cost. Similar findings have been reported by several researches [31,32,33]. Again, Table 2 exhibits that the sigma square (0.052) of the estimated model is statistically significant at 1% level of probability.…”
Section: Empirical Results Of the Stochastic Production Frontier Modelsupporting
confidence: 88%
“…Advisory service rendered to the farmers in general can help farmers to improve their average performance in the overall farming operation as the service widens the household's knowledge with regard to the use of improved agricultural inputs and agricultural technologies. This result is also similar to those obtained by [31] and [33].…”
Section: Determinants Of Technical Inefficiency Among Pineapple Farmesupporting
confidence: 92%
“…The BCR was found as 1.60, which revealed that pineapple production was profitable. The result is similar with Suhaimi and Fatah (2019) and Balogun et al (2018) where the authors declared that being a profitable business, pineapple production could contribute to livelihood improvement of smallholder farmers.…”
Section: Resultssupporting
confidence: 88%
“…Suhaimi and Fatah (2019) conducted a study on pineapple profitability among smallholders in Malaysia and revealed that pineapple production was profitable in the study area with a BCR of 1.72. Similarly, Balogun et al (2018) estimated the pineapple profitability in Ogun State, Nigeria, and found that pineapple production resulted in returning more to the farmers than the original investment in terms of purchased inputs. CDAIS (2018) performed a study on building a public-private pineapple partnership in the Chittagong hill tracts, which resulted in an effective new pineapple grower's association with competent and confident leaders and better-off members.…”
Section: Introductionmentioning
confidence: 99%
“…Mango was found to be the least technically efficient crop among the studied, with a mean TE of 0.596±0.11 [52]. Pineapple is the most unpredictable crop among the fruits studied resulting an average TE of 0.67 with a standard error of 0.25 [53][54][55][56][57].…”
Section: Resultsmentioning
confidence: 99%